Religious Moderation Values Implementation to Early Childhood - Darlis, Ahmad; Nurlaili, Nurlaili; Silaen, Irma Sulistia (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study is about the implementation of religious moderation values in early childhood in Medan City. The study aims to determine the implementation policy of religious moderation, the process of internalizing the values of religious moderation and the achievement of internalization of religious moderation values in early childhood in Medan City. The methodology used in this study is qualitative by conducting interviews, observations and documentation and a combination with literature. The subjects of the study were RA and TK educational institutions selected purposively. The results of the study indicate that the implementation policy in educational institutions is based on internal and external policies. Internal is the implementation of religious moderation values carried out on the basis that it is God's command (religion) and on the basis that humans must indeed be moderate in their attitudes and ways of thinking. This implementation is termed theo-anthropocentric basis (divinity and humanity). As for externally, strengthening the implementation is carried out because there are indeed regulations or rules that require it. The process of internalizing religious moderation values carried out is by integrating learning through images, videos (animation and non-animation), and cultural and religious studies outside of school. The achievement is that early childhood is able to implement religious moderation with four indicators in the foundation phase. Theoretical-practical research recommendations; increasing insight into religious moderation in educational institutions is important to be done periodically.